Folic Acid Supplementation and the Risk of Cardiovascular Diseases: A Meta‐Analysis of Randomized Controlled Trials. Issue 8 (August 2016) - Li, Yanping; Huang, Tianyi; Zheng, Yan; Muka, Tauland; Troup, Jenna; Hu, Frank B.
Abstract : Background: Results from observational and genetic epidemiological studies suggest that lower serum homocysteine levels are associated with lower incidence of cardiovascular disease (CVD). Numerous randomized controlled trials have investigated the efficacy of lowering homocysteine with folic acid supplementation for CVD risk, but conflicting results have been reported. Methods and Results: Three bibliographic databases (Medline, Embase, and the Cochrane Database of Systematic Reviews) were searched from database inception until December 1, 2015. Of the 1933 references reviewed for eligibility, 30 randomized controlled trials involving 82 334 participants were included in the final analysis. The pooled relative risks of folic acid supplementation compared with controls were 0.90 (95% CI 0.84–0.96; P =0.002) for stroke, 1.04 (95% CI 0.99–1.09; P =0.16) for coronary heart disease, and 0.96 (95% CI 0.92–0.99; P =0.02) for overall CVD. The intervention effects for both stroke and combined CVD were more pronounced among participants with lower plasma folate levels at baseline (both P <0.02 for interaction). In stratified analyses, a greater beneficial effect for overall CVD was seen in trials among participants without preexisting CVD ( P =0.006 for interaction) or in trials with larger reduction in homocysteine levels ( P =0.009 for interaction). Conclusions: Our meta‐analysis indicated a 10% lower risk of stroke and a 4% lower risk of overall CVD with folic acid supplementation. A greater benefit for CVD was observed among participants with lower plasma folate levels and without preexisting CVD and in studies with larger decreases in homocysteine levels. Folic acid supplementation had no significant effect on risk of coronary heart disease.